Kampanye Media Sosial untuk Meningkatkan Awareness Upcycling Crochet - Kyna, Zefanya; Yusuf, Vanessa; Malkisedek, Mendy Hosana (Universitas Negeri Jakarta, 2025)
The growing phenomenon of fast fashion has triggered negative impacts on the environment, such as pollution from textile waste and the excessive exploitation of natural resources. The lack of public education regarding the dangers of fast fashion has worsened this situation. This study aims to raise public awareness about the dangers of fast fashion and offer upcycling solutions through the Oopsycle social media campaign. This qualitative research uses data collection techniques through interviews and observations. Interviews were conducted with the general public who are familiar with fast fashion practices. Observations were made during the Oopsycle social media campaign activities and upcycling events. The Oopsycle social media campaign is expected to effectively raise public awareness about the dangers of fast fashion and the upcycling solution. It is also hoped that this study can contribute to addressing the fast fashion problem and encourage society to switch to more sustainable alternatives.